Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Using equivalent and fundamenta. angles, we find that:
a) [tex]\sin{\left(\frac{4\pi}{3}\right)} = \frac{\sqrt{3}}{2}[/tex]
b) [tex]\cos{\left(\frac{11\pi}{3}\right)} = \frac{1}{2}[/tex]
c) [tex]\sin{\left(-\frac{5\pi}{3}\right)} = -\frac{1}{2}[/tex]
d) [tex]\cos{\left(-\frac{2\pi}{3}\right)} = -\frac{1}{2}[/tex]
Item a:
[tex]\frac{4\pi}{3}[/tex] is an angle in the third quadrant, as [tex]\pi < \frac{4\pi}{3} < \frac{3\pi}{2}[/tex]
It's equivalent in the first quadrant is: [tex]\frac{4\pi}{3} - \pi = \frac{\pi}{3}[/tex], which is a fundamental angle, which means that it's values of sine, cosine and tangent are known.
Sine in the third quadrant is negative, while in the first is positive, thus:
[tex]\sin{\left(\frac{4\pi}{3}\right)} = -\sin{\left(\frac{\pi}{3}\right)} = \frac{\sqrt{3}}{2}[/tex]
Item b:
[tex]\frac{11\pi}{3} = 2\pi + \frac{5\pi}{3}[/tex]
Thus, it is equivalent to an angle of [tex]\frac{5\pi}{3}[/tex], which is in the fourth quadrant.
It's equivalent on the first quadrant is:
[tex]2\pi - \frac{5\pi}{3} = \frac{\pi}{3}[/tex]
Cosine in the fourth quadrant is positive, just as in the first, thus:
[tex]\cos{\left(\frac{11\pi}{3}\right)} = \cos{\left(\frac{\pi}{3}\right)} = \frac{1}{2}[/tex]
Item c:
[tex]2\pi - \frac{5\pi}{6} = \frac{7\pi}{6}[/tex]
Which is a angle in the third quadrant.
It's equivalent in the first is:
[tex]\frac{7\pi}{6} - \pi = \frac{\pi}{6}[/tex]
Sine in the third quadrant is negative, while in the first is positive, thus:
[tex]\sin{\left(-\frac{5\pi}{6}\right)} = \sin{\left(\frac{7\pi}{6}\right)} = -\sin{\left(\frac{\pi}{6}\right)} = -\frac{1}{2}[/tex]
Item d:
[tex]2\pi - \frac{2\pi}{3} = \frac{4\pi}{3}[/tex]
Which is in the third quadrant.
Cosine in the third quadrant is negative, while in the first is positive, thus:
[tex]\cos{\left(\frac{-2\pi}{3}\right)} = \cos{\left(\frac{4\pi}{3}\right)} = -\cos{\left(\frac{\pi}{3}\right)} = -\frac{1}{2}[/tex]
A similar problem is given at https://brainly.com/question/23843479
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.